Gambaran Hasil Pemeriksaan HIV pada Darah Donor - Bagus Triatmojo (Poltekkes Kemenkes Semarang, 2020)
HIV cases in Jepara District in recent years have demanded the handling of several aspects simultaneously including the Blood Transfusion Unit (BTU). HIV can be transmitted through blood transfusion or other blood products. BTU of PMI Jepara Regency carries out recruitment of voluntary donor from Jepara society. The HIV examination as part of an IMLTD screening test is done for safety of donor blood. The HIV examination in all donor blood uses rapid and elisa method. Examination results are stated as reactive and non reactive. Research objective to find out the description of HIV examination results in donor blood at the BTU of PMI Kabupaten Jepara in 2019. Research method the research type was descriptive using records of donor data at BTU of PMI Kabupaten Jepara in 2019. The examination results of reactive HIV in 12 donor blood (0,08%). non-reactive blood donor of HIV in age groups 18 years, 18-24, 25-44, 45-59, and ≥ 60 years respectively 9,55%, 22,39%, 51,75%, 16,01% and 0,21%. Reactive HIV in age groups 18-24, 25-44, and 45-59 years were 0,034%, 0,034%, and 0,13%. Non-reactive HIV in men 68,22% and in women 31,70%. Reactive HIV in men 0,07%, and women 0,01%. Non-reactive HIV in voluntary donor blood was 99,779% and substitute donor was 0,127%. HIV of reactive voluntary donor blood was 0,074%, and substitute donor was 0,007%. HIV filter test is indispensable for blood safety because the age, gender and blood type of donors have the potential for reactive HIV.